Integrated STEM Approach to Improve 21st Century Skills in Indonesia: A Systematic Review - Lafifa, Fitria; Rosana, Dadan; Suyanta, Suyanta; Nurohman, Sabar; Dwi Astuti, Sri Rejeki (International Journal of STEM Education for Sustainability, 2023)
21st-century skills are important for students to be equipped to face the challenges of the 21st century. So it needs an appropriate approach to be able to provide resources that are by the demands of the 21st century. This study aimed to determine the influence of STEM approaches in science learning to improve students' 21st-century skills and determine the indicators of STEM elements in science learning. The method used in this study is a literature study or a study of research results from several journals. The instrument used is a Paper Classification Form (PCF) table. The data were analyzed using percentages and descriptive calculations. The study results showed that n methods are often used in STEM approaches to improve century skills by using a STEM approach only, followed by a combination of various learning models such as inquiry, PBL, and PjBL. K21st century skills most often studied are students' critical thinking skills. Indicator of STEM approaches in science learning includes Science, which is related to natural symptoms and observation; technology is related to the use of tools; Engineering is related to designing to make solutions; and Mathematics is related to linkage analysis. The STEM approach is very influential in improving students' 21st-century skills: communication, creativity, critical thinking, and collaboration.